Prenatal Marijuana Use by Self-Report and Umbilical Cord Sampling in a State With Marijuana Legalization. Issue 1 (January 2019) - Metz, Torri D.; Silver, Robert M.; McMillin, Gwendolyn A.; Allshouse, Amanda A.; Jensen, Triniti L.; Mansfield, Chanel; Heard, Kennon; Kinney, Gregory L.; Wymore, Erica; Binswanger, Ingrid A.
Abstract : OBJECTIVE: To compare self-reported maternal marijuana use with quantitative biological sampling for a marijuana metabolite, 11-nor-delta-9-tetrahydrocannabinol-9-carboxylic acid, in umbilical cord homogenate in a state with legalized marijuana. METHODS: We conducted a cross-sectional study of women approached at the time of admission for delivery with live, singleton pregnancies at 24 weeks of gestation or greater at two urban medical centers in Colorado. Maternal marijuana use was estimated by 1) report to a health care provider on admission history and physical, 2) survey of self-reported use, and 3) liquid chromatography–tandem mass spectrometry analysis of umbilical cord homogenate for 11-nor-delta-9-tetrahydrocannabinol-9-carboxylic acid. Women were categorized by survey-reported last use (30 days ago or less, 30 days to 1 year, more than 1 year, never) and proportion of women with cord results above the limit of detection and limit of quantification for 11-nor-delta-9-tetrahydrocannabinol-9-carboxylic acid was reported for each group. Comparisons between groups were made using contingency tables. Correlation between survey-reported frequency of use and quantitative 11-nor-delta-9-tetrahydrocannabinol-9-carboxylic acid cord homogenate results was evaluated. RESULTS: We included 116 women with self-report surveys linked to cord assay results. Six percent (95% CI 2.5–12.0%) of participants reported use in the past 30 days on survey and 2.6% (95% CI 0.5–7.4%) of participants reported marijuana use to health care providers. On umbilical cord assay, 22.4% (95% CI 15.2–31.1%) had detectable 11-nor-delta-9-tetrahydrocannabinol-9-carboxylic acid. The proportion of women with detectable 11-nor-delta-9-tetrahydrocannabinol-9-carboxylic acid increased with more recent self-reported use. Survey-reported frequency of use in the past 30 days had moderate correlation with quantified umbilical cord 11-nor-delta-9-tetrahydrocannabinol-9-carboxylic acid (correlation coefficient 0.44, 95% CI 0.28–0.58, P <.001). CONCLUSION: Umbilical cord sampling results in higher estimates of prenatal marijuana use than self-report even in the setting of legalization. Umbilical cord assays for 11-nor-delta-9-tetrahydrocannabinol-9-carboxylic acid demonstrate promise for quantifying use. Future studies should examine how the use of biological sampling informs the association between marijuana use and perinatal outcomes. Abstract : Umbilical cord sampling for marijuana metabolites detected prenatal marijuana use at a higher rate than self-reported estimates, even in a state with legalized marijuana.